The Distribution of Metadiscourse Markers in Texts of English Trade Agreements - Najeeb, Alyaa Farooq; Rezqallah, May Stephan (Al-Adab Journal, 2022)
Metadiscourse markers refer to the linguistic elements that establish a relationship between the writers and the readers, the current study has conducted a quantitative analysis to measure the distribution and frequencies of metadiscourse markers in the texts of English trade agreements. The study has adopted the classifications of Hyland (2005); these classifications been applied to four English trade agreements obtained from official websites; four extracts have been selected randomly from each agreement. The results of the study have revealed that the English agreements used Interactive markers more than interactional markers.